THE RELATIONSHIP BETWEEN MOTIVATION IN LEARNING ENGLISH TOWARDS STUDENTS’ LEARNING ACHIEVEMENT AT THE ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Leny Ferayanti (FPB PBI 16 UMY 005, 2016)
This research aims to find students’ motivation, revealing the students’ learning achievement and investigating the relationship between motivation in learning English towards students’ learning achievement at the English Education Department of Universitas Muhammadiyah Yogyakarta. There were 49 students’ batch 2012 at the English Education Department of Universitas Muhammadiyah Yogyakarta who participated in this research. There were two instruments, i.e. questionnaire and document. The questionnaire was statistically analyzed by using the SPSS 22.0 windows. To measure the students’ learning achievement, it used the GPA (Grade Point Average) as the document from the students at batch 2012 at the English Education Department. The Pearson product moment correlation coefficient was used to see the relationship between the two variables (motivation and learning achievement). Findings from this research showed that the motivation in learning English of students at batch 2012 was very high and dominant for instrumental motivation and the learning achievement of students at batch 2012 is at distinction level. There was a significant relationship between motivation in learning English and students’ learning achievement. In conclusion, the variables of this research show that motivation in learning English has positive relationship towards students’ learning achievement. That is why alternative hypothesis (H1) was accepted.